The Constraint of a Rhetorical Invention: Kwame Nkrumah and the Organization of African Unity - Opoku, Mensah Eric (Lagos Notes and Records, 2020)
Rhetorical constraints have the potential to inhibit a successful communication transaction. How they do that sometimes practically remains unclear, especially within the study of rhetoric in the African context. This paper examines Kwame Nkrumah’s rhetorical urgency as an argumentative tool for the establishment of an organization which would direct the political, economic and military directions of Africa. Employing Bitzer’s Situation (1968) and Meyer’s Composite Audience (1999) as analytical framework, the paper takes a critical look at Nkrumah’s rhetorical invention to locate the inherent constraints and how they (constraints) eclipsed the total success of Nkrumah’s invention. This study therefore has implications for the episteme of the different contexts within which rhetorical inventions are created and performed within the pan African liberation sphere.
Research Article
Keywords: Nkrumah, Rhetoric, OAU, Pan Africanism, Colonialism